Serial propagation of Pneumocystis carinii in cell line cultures. - Latorre, C R (1977)
Pneumocystis carinii was propagated on three cell lines routinely cultured in many laboratories; the method is practical and convenient. Organisms produced were found to be reactive to Pneumocystis antisera. Studies of antigenic relationships, life cycles, and diagnostic methods will be made easier by these cultures.